La « distance proximale » à l'épreuve du dispositif « Ma classe à la maison » - Isabelle Jugé-Pini; Jean-François Plateau; Bernard Coulibaly (Université de Provence, 2022)
The aim of our study is to identify the socio-educational and affective effects of the first Covid-19-related confinement on the pedagogical relationship. In the educational field, the principle of "pedagogical continuity" required the implementation of the "My class at home" scheme. We therefore observe the feelings of teachers and pupils through the notion of "proximal distance" (Paquelin, 2011). A qualitative and quantitative survey conducted among teachers and 106 high school students supports the following questions: Does "distance" produce proximity? What role do emotions play in the teacher-student relationship? Can this experience have lasting effects on distance support? The results provide avenues for reflection on: a) the paradox of proximity at a distance; b) the recognition of the place of emotions in the triangular student-teacher-knowledge relationship; c) the limits of the transferability of the distance experience to secondary school teaching practices outside the health context.